Comparison of the corrosion performance of alloys HP40 and T22 exposed to molten salts at high temperature - Cuevas Arteaga, Cecilia; Clemente, Christian; Sotelo-Mazón, Oscar; Ramírez Rodríguez, José Alfredo (2021)
The molten salt corrosion performance of SS-HP40 with high Cr content and carbon steel T22 with low Cr content were investigated. The corrosion behavior was obtained using three techniques: potentiodynamic polarisation curves (PC), electrochemical noise (EN) and the mass loss method (ML). XRD and SEM were utilized to characterize the oxide scales formed over the metallic surfaces. Alloys were exposed to 80% mol V2O5-20Na2SO4 mixture at 550°C and 650°C during 5 days. The corrosion rates of EN and ML agreed, showing to be thermally activated. SEM images showed that both materials suffered pitting corrosion in spite of HP40 has a great content of Cr. This result was due to high vanadium molten salt is very oxidant and acid, favoring a major dissolution of the Cr2O3 presents on HP40 and Fe2O3 formed on T22. Secondary corrosion products at low fusion points lead an increase in fluidity, which exacerbates the oxidation reactions.